DEVELOPMENT OF BAND-SPLIT RNN AND HYBRID TRANSFORMER DEMUCSFOR MUSIC SOURCE SEPARATION - Kalang Al Qalyubi, Ken
In recent years, models have been developed in the field of music source separation (MSS). The current state-of-the-art models are Hybrid Transformer Demucs (HT